Ramsay Hunt Syndrome in Asymptomatic COVID-19 Infection: A Case Report and a Literature Review - Ayoub, Wissam Al Rida (2023)
(1) Background: COVID-19 infection has affected almost 6 million people worldwide. Geniculate Ganglion Zoster resulting in Ramsay Hunt Syndrome (RHS) has been rarely described in this context. (2) Methods: Here, a case of RHS in the context of asymptomatic COVID-19 infection is reported followed by a literature review of the previously published cases (PubMed research combining “COVID-19” and “Ramsay Hunt Syndrome” or their abbreviations/synonyms, searching for data published at any time till October 2023). (3) Results: Five cases have been previously published (age range: 25–67 years; n = 3 males). Three patients were known to be immunocompetent prior to infection, one was receiving corticotherapy for lung disease, and one had an unspecified immune status. RHS predominantly involved both facial and vestibulocochlear nerves, with one case exclusively involving the facial nerve as the presented case. Regarding facial nerve palsy, three were right-sided (like the current report) and two were left-sided. Two cases were asymptomatic to COVID-19 (like the present patient), one had mild fatigue, and two had classical COVID-19 symptoms preceding RHS symptoms. Workup included serological testing against Varicella Zoster Virus and PCR assays that can detect the viral DNA in saliva, blood, tears, exudates, and cerebrospinal fluid. The treatment combined antiviral and corticosteroid therapies which yielded heterogeneous outcomes that might be related to some demographic and clinical data. (4) Conclusions: RHS rarely occurs in the context of COVID-19. Early recognition is important. Management seems to be similar to the classical condition. Some data may help predict facial nerve recovery.